Workshops in International Conference on Social Robotics (UTS ePRESS, 2014)
This is a collection of the papers presented during the workshop sessions at the International Conference on Social Robotics 2014. In this edition are collected the contributions for the following workshops: • Robots and Art - Misbehaving Machines • Attention for Social Intelligence